The Spook's Bestiary : the guide to creatures of the dark - Delaney, Joseph, 1945- (Delaney, Joseph, 1945- Last apprentice., 2011)
Ready to be presented to the last apprentice, Tom Ward, the spook's notebook contains instructions for vanquishing boggarts, witches, the unquiet dead, and other dark creatures and spirits.